UNDERSTANDING THE MECHANISM OF JOINT PROPERTY DIVISION: RIGHTS OF HUSBAND AND WIFE ACCORDING TO MARRIAGE LAW IN INDONESIA - Royani, Esti; Kamaluddin; Sarikun; Isnawati; Syamsudin (Awang Long Law Review, 2025)
The mechanism for dividing joint assets in marriage law in Indonesia still occurs due to differences in its implementation. Court decisions often rely on consideration of financial contributions, but non-financial contributions are not properly recognized. Inaccuracies in judges' decisions and the lack of public understanding of the law are the main factors influencing the uncertainty of the division of joint assets after divorce. This study aims to analyze the mechanism of division of joint property in marriage law in Indonesia and identify the factors that influence the process. The focus of this study is to examine financial and non-financial contributions considered in court decisions, and differences in legal interpretation can affect the results of the division of joint assets. This study uses empirical research methods with qualitative and quantitative approaches. A total of 30 divorce cases have been analyzed in district courts and religious courts to understand the pattern of division of joint assets in legal practice. The results of the study show that although most court decisions prioritize financial contributions in the division of joint assets, non-financial contributions have not been estimated. Other influencing factors are property owners, access to legal examination, and recognition of two rights. More comprehensive rules and regulations are needed for the distribution of joint assets. An important step towards a fair and transparent legal system is the reform of the judicial system and legal training for married couples.